Universitas Jember Kampus Kebangsaan; Pengembangan Kreativitas dan Apresiasi Seni Mahasiswa melalui UKM Kesenian - Syavira Ainur Rohma; Kania Rahma Meneling; Nisa Urrosidah; Muhammad Irfan Ardiansyah; Yudha Nurdian (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2024)
Art is an expression of the human spirit and culture used in showing beauty. Art is one of the fields that many students master, one of which is university students. The University of Jember facilitates the interests and talents of students in the field of Art with the establishment of the Art Student Activity Unit (UKM Kesenian). This research contains about the University of Jember Arts UKM, preservation and appreciation of Indonesian culture through Arts UKM. This study aims to (1) describe the Art Student Activity Unit, (2) analyze the questionnaire data and describe development of creativity,  and appreciation of the art of Jember University students. This research uses quantitative and qualitative methods with a descriptive approach. Primary and secondary data collection was carried out using observation, qualitative visuals, questionnaires, literature review, and direct interviews. Questionnaire is a way of collecting data that contains a series of questions distributed to students. Interview is an activity between two or more people to get information. Based on the results and discussion, it can be concluded that the development of creativity through UKM Arts is considered efficient and effective as evidenced by the implementation of work programs and achievements achieved by members of UKM Arts. Appreciation through UKM Arts is carried out by many students joining as members and participating as spectators. Appreciation not through UKM Arts is expressed by appreciation of batik, namely by using batik while studying.